CONE-BEAM COMPUTED TOMOGRAPHY EVALUATION OF DENTOSKELETAL EFFECTS PRODUCED BY THE BONDED EXPANDER AND HYRAX: A PILOT STUDY - Almeida, Guilherme de Araujo; Santos Menezes, Joana Cristina dos; Lelis, Everton Ribeiro [UNESP]; Roscoe, Marina Guimaraes; Mundim Prado, Isadora Moraes; Machado, Asbel Rodrigues; Fernandes Neto, Alfredo Julio (Univ Federal Uberlandia, 2016)
The dentoskeletal effects produced by the bonded expander, principally the vertical ones, are controversial in the literature when compared with the effects produced by the hyrax, and have also been scarcely studied by means of cone-beam computed tomography (CBCT). This study aimed to evaluate the horizontal and vertical dentoskeletal effects produced by the bonded expander and by the hyrax using CBCT. The study sample consisted of ten patients, divided equally into two groups according to facial and cephalometric features: group 1, vertical facial growth pattern (two males, three females; mean age, 7.7 years) and group 2, normal facial growth pattern (three males, two females; mean age, 8.3 years), treated by bonded expander and hyrax, respectively. The patients were subjected to a CBCT scan before expansion and another scan four months after the end of the activations, when the expander was removed. Within each group and between the groups the horizontal and vertical effects were assessed using Student's t-test. The sample size was predetermined, and 5 patients were needed in each group to detect the differences at P < 0.05 with 90% power. Among the horizontal changes assessed, the nasal floor width (P = 0.03) and the greater internal width in the posterior region (P = 0.00) showed a statistically significant increase only for group 1, and the mandibular molar verticality showed a statistically significant increase only for group 2. The vertical changes showed no statistical differences within groups (P > 0.05). Comparing the two groups there were no statistical differences for any assessed change (P > 0.05). Considering there were no differences of the effects between the appliances, the bonded expander produced no greater vertical control compared to the hyrax. Nevertheless, further study is recommended in a larger sample size using CBCT.
Keywords: Orthodontic Appliances; Palatal Expansion Technique; Malocclusion